Identifikasi Penentuan Prioritas Kriteria Perumahan dan Permukiman Kumuh Menggunakan Metode AHP (Analytical Hierarchy Process) - Fitriani Rahmawati; Andi Ahdan Amir; Abdul Fattaah Mustafah (Jurnal Malige Arsitektur, 2020)
The government has ratified the Ministerial Regulation NO. 14 / PRT / M / 2018 to improve the quality of life and livelihoods of the community through the implementation of healthy, safe, harmonious and orderly housing and settlement areas to prevent the growth and development of slum housing and slum settlements. The ministerial regulation has stated the criteria used to determine slum conditions in slum housing and slum settlements. This study aims to determine what criteria are prioritized in the process of determining housing and slum settlements in the research area, and to determine the application of the Analytical Hierarchy Process (AHP) method in providing weighting criteria and setting more specific priorities. This study aims to determine what criteria are prioritized in the process of determining housing and slum settlements in the research area, and to determine the application of the Analytical Hierarchy Process (AHP) method in providing weighting criteria and setting more specific priorities. AHP method is used to analyze the criteria that affect the priority determination of housing and slum settlement criteria. The criteria that are very influential in determining the identification of housing and slum settlements in the study area, namely the criteria for the availability of safe access to drinking water (0,082), unfulfilled drinking water needs (0,082), availability of drainage (0,078), inability of drainage to drain water runoff (0,078), quality of drainage construction (0,078) and coverage of environmental road services (0,074).Keywords: Criteria, Housing and Slums, AHP